Nasal Polyps :An Etiological Analysis (Indian Journal of Forensic Medicine & Toxicology, 2020)
Nasal polyps,the prolapsed linings of nasal mucosa are one of the commonly encountered conditions in theoutpatient department of otolaryngology, The aim of this study is to study the etiology of nasal polyps andalso to compare between the different methods used for diagnosis of nasal polyps.This study was submitted prospectively on 100 patients diagnosed with nasal polyps (diagnosed eitherclinically or radiologically) with evidence of nasal obstruction,rhinorrhae and headache. from April 2015till April 2017. All patients had been selected from the outpatient clinics of Al-Zahraa University Hospitaland Kobry El Koppa military hospital. The study was approved by the ethics committee of Al Azhar Facultyof Medicine.A total of 100 patients were analyzed, age range 18 to 56 yrs with a mean age of 38.5 yrs. There were 83 maleand 17 female. The main presenting symptoms are nasal obstruction and rhinorrhea. Most of the cases wasbilateral nasal polyps,. The commonest clinical diagnoses were non-neoplastic simple nasal polyps 84% andabout 13% were benign neoplastic, 3% were malignant . The commonest histological diagnosis among nonneoplastic nasal polyps was simple allergic nasal polyp, among benign neoplastic was inverted papilloma.most of neoplastic lesions were presented by unilateral nasal polyps,where epistaxis was noticed mostlywith vascular tumour and malignant ones. The results show that most of nasal polyps were simple nonneoplastic lesions especailly bilateral ones,also for proper evaluation of nasal polyps clinical, radiologicaland histopathological evaluation should be done in all patients.
Keywords: nasal polyps,histopatholgy, inverted papilloma.